Buletin Peternakan : PENGARUH INOKULUM CAMPURAN Lactobacillus plantarum DAN Saccharomyces cerevisiae TERHADAP KUALITAS ORGANOLEPTIK, FISIK, DAN KIMIA SILASE KULIT BUAH KAKAO - Muhammad Askari Zakariah, Ristanto Utomo, Zaenal Bacruddin (Peternakan UGM, 2015)
This research was done to determine the effect of L. plantarum and S. cerevisiae innoculated into cocoa pod silage on organoleptic, physical and chemical quality. This experiment consist of four treatments namely silage of fresh harvested cocoa pods without inoculant as control (K); inoculated with L. plantarum (KLp); innoculated with S. cerevisiae (KSc); and innoculated with both L. plantarum and S. cerevisiae mixture (KLp+Sc) was cassava meal added as supplement. Each treatment was replicated 3 time. Ensilage was done for 21 days